2012
DOI: 10.1262/jrd.2011-006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Double-knockout Mouse Sperm Lacking SPAM1 and ACR or SPAM1 and PRSS21 in Fertilization

Abstract: Abstract. Mammalian fertilization requires sperm to penetrate the cumulus to reach the oocyte. Although sperm hyaluronidase has long been believed to participate in the penetration process, our previous works revealed that neither of two sperm hyaluronidases, SPAM1 and HYAL5, are essential for fertilization. In this study, we have produced doubleknockout mice lacking SPAM1 and either one of two sperm serine proteases, ACR and PRSS21, and characterized the mutant sperm. The SPAM1/ACR-and SPAM1/PRSS21-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Rat anti‐IZUMO1 monoclonal antibody (Mab125) (Ikawa et al, ; Inoue et al, ) was generously provided by Dr. M. Ikawa (Osaka University, Japan). Goat anti‐IZUMO1 polyclonal antibody (item sc‐79539) and rat anti‐ZP2 monoclonal antibody (clone IE‐3; item sc‐32752) (Zhou, Kang, & Baba, ) were purchased from Santa Cruz Biotechnology (Dallas, TX). Alexa Fluor 568‐conjugated PNA (item L32458) or Alexa Fluor 568‐conjugated phalloidin (item A12380) and secondary antibodies were purchased from Molecular Probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat anti‐IZUMO1 monoclonal antibody (Mab125) (Ikawa et al, ; Inoue et al, ) was generously provided by Dr. M. Ikawa (Osaka University, Japan). Goat anti‐IZUMO1 polyclonal antibody (item sc‐79539) and rat anti‐ZP2 monoclonal antibody (clone IE‐3; item sc‐32752) (Zhou, Kang, & Baba, ) were purchased from Santa Cruz Biotechnology (Dallas, TX). Alexa Fluor 568‐conjugated PNA (item L32458) or Alexa Fluor 568‐conjugated phalloidin (item A12380) and secondary antibodies were purchased from Molecular Probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…Blocked samples were incubated with anti‐IZUMO1 antibody (1:200 dilution of Mab125) and Alexa Fluor 488 rabbit anti‐rat IgG plus Hoechst 33342, as described above (section 4.4). Fluorescence images were captured using an Extended Depth of Focus z‐axis motor (Nikon Products), and processed by NIS‐AR software (Nikon Co.), as described previously (Zhou et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, a neutralizing antibody to rHuPH20 could cross-react with human PH20, inhibiting this activity. However, studies of PH20 knockout mice immunocontraceptive trials with anti-PH20 antibodies in mice and rabbits have shown that it plays a nonessential role in fertility [27][28][29][30]. Large doses of rHuPH20, such as those used to elicit high titers of neutralizing anti-rHuPH20 antibodies in animal studies, did not result in an observable effect on fertility, reproduction, fetal development or postnatal life [31].…”
Section: Recombinant Human Hyaluronidasementioning
confidence: 99%
“…The authors suggest a role in cumulus dispersal and penetration, which is interesting since sperm lacking known hyaluronidases SPAM1 (Baba et al 2002) and HYAL5 (Kimura et al 2009) were able to fertilize oocytes. Together with double knockout experiments of SPAM1 and ACR or SPAM1 and PRSS21 (Zhou et al 2012), these results suggest that ACR and PRSS21 may work in concert with hyaluronidases for cumulus penetration. These results are also consistent with the notion that acrosomal exocytosis occurs before or during interaction with the cumulus (Jin et al 2011).…”
Section: 5 Oocyte Cumulus Complex and Zona Pellucida Transit: Protementioning
confidence: 74%